ANALISIS PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA PADA PT NUSANTARA SURYA SAKTI (NSS) DEALER BALIKPAPAN - Alifah Shawalia; C. Prihandoyo; Nadi Hernadi Moorcy (Fakultas Ekonomi Universitas Balikpapan, 2023)
The purpose of this study was to determine the influence of Culture, Social, Personality, and Psychology on purchase decisions for Honda motorbikes at PT. Nusantara Surya Sakti (NSS) Balikpapan Dealer. This research was conducted at PT. Nusantara Surya Sakti (NSS) Balikpapan Dealer, with 210 respondents, this research method used quantitative. Data collection by means of interviews, observation, and distribution of questionnaires via google form. The data analysis technique used is multiple linier analysis by conducting instrument test, classical assumption tests, and hypothesis testing. The test results show that the cultural, social, personality, and psychological variables have a positive and significant effect on the decision to purchase a honda motorbike at PT. Nusantara Surya Sakti (NSS) Balikpapan Dealer.